Law Enforcement Of The Crime Of Illegal Fishing In The Waters Area Of Pangkajene Regency And The Islands - Muhammad Fauzi Ramadhan; Abd. Asis; Audyna Mayasari Muin (LEGAL BRIEF, 2022)
Law enforcement of illegal fishing in the waters of Pangkajene and the islands has not been effective. This research is an empirical normative research, combining the normative legal approach to legislation with empirical elements in the form of interviews. The results of the study show that law enforcement of criminal acts in the field of fisheries in the Pangkajene and archipelagic waters has not been effective, this is due to a conflict of norms between one regulation and another related to the marine and fisheries sector, which causes law enforcement officers to find it difficult to implement which rules to enforce. In addition, the existence of an ego-sectoral relationship between law enforcement officers causes law enforcement to still not go hand in hand with each other and the ability of prosecutors and judges to complete the mighty crime of illegal fishing in the Pangkajene and Kepualuan districts.